2019
DOI: 10.4314/ovj.v8i4.18
|View full text |Cite
|
Sign up to set email alerts
|

Survey of bovine tuberculosis in Nigerian beef cattle

Abstract: Bovine tuberculosis (bTB) is a zoonotic disease caused by Mycobacterium tuberculosis complex (MTBC) that primarily affects cattle, but also other domestic and wild mammals. In Nigeria, abattoir monitoring of gross bTB lesions is the only control method being applied in all animals. This study aims to investigate tubercle bacilli infection in slaughtered cattle found with visible tuberculosis-like lesions. Lesions suggesting bTB were detected in 226 cattle during abattoir monitoring in Zamfara State, Nigeria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Another possible reason is that imported cattle are less resistant to TB infection than local breed [22], which can make imported cattle at high risk of infection. On the other hand, the result showed that the odds of TB were greater in female, compared to male, which is in line with what was previously reported by Worku et al (2016) [23] and Ahmad et al (2018) [24] . The stress of calving and lactation might decreasefemale immunity and makes them at high risk of infection.…”
Section: Discussionsupporting
confidence: 92%
“…Another possible reason is that imported cattle are less resistant to TB infection than local breed [22], which can make imported cattle at high risk of infection. On the other hand, the result showed that the odds of TB were greater in female, compared to male, which is in line with what was previously reported by Worku et al (2016) [23] and Ahmad et al (2018) [24] . The stress of calving and lactation might decreasefemale immunity and makes them at high risk of infection.…”
Section: Discussionsupporting
confidence: 92%
“…M . caprae was previously isolated from bovine TB in Algeria and other African countries [ 25 , 26 , 38 , 45 ]. The infection of cattle by M .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding M. caprae, we identified two types (SB0835 and SB1451) from cattle in two slaughterhouses. M. caprae was previously isolated from bovine TB in Algeria and other African countries [25,26,38,45]. The infection of cattle by M. caprae could be explained by the cohabitation with goats [15].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The published epidemiological studies show that M. bovis is identified worldwide (1,3). In most cases, M. bovis is transmitted between animals in the same herd in aerosols.…”
Section: Discussionmentioning
confidence: 99%